Crucified Wisdom: Theological Reflection on Christ and the Bodhisattva, by Mark S. Heim. - Syndor, Jon Paul (Interreligious Studies and Intercultural Theology, 2020)
Crucified Wisdom: Theological Reflection on Christ and the Bodhisattva, by Mark S. Heim. Fordham University Press, 2019.